Clinico‐biochemical investigations of aging effects on normoglycemic and hyperglycemic murine retinal tissues. Issue 12 (11th September 2014) - Shin, Jae‐Ho; Choi, Jeong Han; Choi, Samjin; Jung, Gyeong Bok; Park, Hun‐Kuk; Moon, Sang Woong
ABSTRACT Purpose This study used five clinical assessments and Raman spectroscopy to investigate the age‐ and hyperglycemia‐related properties of the murine retina over an eight‐week experimental period. Method Acute hyperglycemia and chronic hyperglycemia were assessed with blood glucose (BG) and glycated hemoglobin (HbA1c) levels, respectively. Changes in the retinal thickness and neovascularization were evaluated with optical coherence tomography and fluorescein angiography (FAG). Histological changes in the retina were studied after periodic acid‐Schiff (PAS) staining. Raman spectroscopy was used to examine the molecular structures and chemical compositions of the retinal tissues. Results The young hyperglycemic group had acute hyperglycemia with a BG level of 576 ± 22 mg/dL and HbA1c of 5.9 ± 0.6%, while the aged hyperglycemic group displayed chronic hyperglycemia with a BG level of 607 ± 28 mg/dL and HbA1c of 11.2 ± 1.5%. Aged hyperglycemic retinas showed an insignificant (5%) decrease in thickness and no presence of vascular leaky lesions with FAG. There was no histological evidence of the retinal neovascularization with PAS staining of these aged hyperglycemic retinas. In the aged group, Raman intensities assigned to the C–C symmetric breathing of the aromatic ring in phenylalanine (1003 cm−1), the NH2 amide III α‐helix deformation in the protein structure (1265 cm−1), and the C=O stretching vibration of amide I α‐helix structure in collagen (1657 cm−1) were all decreased. Conclusion These decreased Raman intensities indicate elevated reactive oxygen species (ROS) and oxidative damage to proteins such as those involved in cell apoptosis. A decrease in these ROS‐related Raman peaks indicates an aging effect on the retina. Microsc. Res. Tech. 77:1023–1030, 2014. © 2014 Wiley Periodicals, Inc.